Unused Parts of Jackfruit (Artocarpus heterophyllus): Prospective In Vitro Antioxidative Activity - Insanu, Muhamad; Pramasatya, Hegar; Buddhisuharto, Anastasia Karina; Tarigan, Chrisanta; Zahra, Aliya Azkia; Haniffadi, Ariranur; Sabila, Nurma; Fidrianny, Irda (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Free radical is unstable and highly reactive, which may lead to oxidative stress that causes various diseases, that is, diabetes mellitus. Antioxidant can prevent oxidation process by scavenging free radicals. Jackfruit (Artocarpus heterophyllus) is a native tropical fruit that can easily be found in Indonesia. When the flesh is commonly eaten, the unused parts – such as the leaves, fruit peels, and pulps will be considered waste to be thrown away. However, these unused parts of Jackfruit are rich in antioxidant compounds that potentially can work as therapeutic agents. AIM: The aim of the study was to determine the antioxidant properties of leaves, peels, and pulps of A. heterophyllus by calculating their antioxidant activity index (AAI) with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Cupric Ion-Reducing Antioxidant Capacity (CUPRAC) method; total phenolic content (TPC) and total flavonoid content (TFC); observing the correlation between TPC and TFC with AAI DPPH and CUPRAC; as well as the correlation between AAI DPPH and CUPRAC. MATERIALS AND METHODS: Extraction process was carried out using reflux method using three different polarity solvents. UV-visible spectrophotometer was used to determine the TPC, TFC, AAI DPPH, and AAI CUPRAC. Pearson’s method was used to observe the correlation between TPC and TFC with AAI DPPH and CUPRAC, as well as the correlation between both methods. RESULTS: The AAI in DPPH method were varied from 0.0310 to 36.8852, while CUPRAC from 0.1156 to 1.2503. Ethanol leaves extract gave the highest TPC value (5.53 g GAE/100 g) and n-hexane peels extract exposed the highest TFC value (16.07 g QE/100 g). The correlation between TPC and AAI of leaves, peels, and pulps extracts with DPPH method, as well as between TFC and AAI CUPRAC of peels extracts was positive and significant. Rutin was determined as the marker compound, valuing at 0.0106%. CONCLUSION: Phenols and flavonoids (including rutin) content contributed to DPPH and CUPRAC antioxidant activity. The antioxidant property between both methods was not linear in leaves, peels, and pulps extracts. Unused parts (peels and leaves) of A. heterophyllus might be potential to be developed as natural antioxidant sources.